The Dolly case, the Polly drug, and the morality of human cloning O caso Dolly, o fármaco Polly e a moralidade da clonagem humana - Fermin Roland Schramm (Cadernos de Saúde Pública, 1999)
The year 1996 witnessed the cloning of the lamb Dolly, based on the revolutionary somatic cell nuclear transfer (SCNT) technique, developed by researchers from the Roslin Institute in Edinburgh, Scotland. This fact marked a relevant biotechnoscientific innovation, with probable significant consequences in the field of public health, since in principle it allows for expanding possibilities for the reproductive autonomy of infertile couples and carriers of diseases of mitochondrial origin. This article expounds on 1) the experiment's technical data and the theoretical implications for the biological sciences; 2) the public's perception thereof and the main international documents aimed at the legal and moral regulation of the technique; and 3) the moral arguments for and against cloning, from the point of view of consequentialist moral theory. We conclude that in the current stage of the debate on the morality of cloning, in which there are no cogent deontological arguments either for or against, weighing the probability of risks and benefits is the only reasonable way of dealing with the issue in societies that consider themselves democratic, pluralistic, and tolerant Em 1996, a ovelha Dolly foi clonada, valendo-se da técnica revolucionária do somatic cell nuclear-transfer (SCNT), desenvolvida por pesquisadores escoceses do Roslin Institute de Edimburgo. Esse fato representa uma inovação biotecnocientífica relevante, com prováveis conseqüências significativas no campo da saúde pública, pois permitirá, em princípio, ampliar as possibilidades da autonomia reprodutiva de casais inférteis e portadores de doenças de origem mitocondrial. Neste artigo, abordam-se 1) os dados técnicos do experimento e as implicações teóricas para as ciências biológicas; 2) a percepção pública no que se refere à clonagem e os principais documentos internacionais que visam a sua regulamentação jurídica e moral; 3) os argumentos morais pró e contra a clonagem, do ponto de vista da teoria moral conseqüencialista. Conclui-se que, no estágio atual do debate sobre a moralidade da clonagem, no qual não existem argumentos deontológicos cogentes, nem a favor nem contra, a ponderação da probabilidade de riscos e benefícios constitui a única maneira razoável de enfrentar a questão em sociedades que se pretendem democráticas, pluralistas e tolerantes.